Biocompatibility of light responsive materials prepared for accommodative intraocular lenses manufacturing - Chen-Zi Liu; Ming-Hao Sun; Wei Dai; Lan-Cao Hao; Si-Quan Zhu (International Journal of Ophthalmology)
AIM: To investigate the biocompatibility and bacterial adhesion properties of light responsive materials (LRM) and analyze the feasibility and biosafety of employing LRM in the preparation of accommodative intraocular lenses (AIOLs). METHODS: Employing fundamental experimental research techniques, LRM with human lens epithelial cells (hLECs) and human retinal pigment epithelium cells (ARPE-19 cells) were co-cultured. Commercially available intraocular lenses (IOLs) were used as controls to perform cell counting kit-8 (CCK-8), cell staining under varying light intensities, cell adhesion and bacterial adhesion experiments. RESULTS: LRM exhibited a stronger inhibitory effect on the proliferation of ARPE19 cells than commercially available IOLs when co-cultured with the undiluted extract for 96h (P<0.05). Under other culturing conditions, the effects on the proliferation of hLECs and ARPE-19 cells were not significantly different between the two materials. Under the influence of light irradiation at intensities of 200 and 300 mW/cm2, LRM demonstrated a markedly higher inhibitory effect on the survival of hLECs compared to commercially available IOLs (P<0.0001). They also showed a stronger suppressive effect on the survival rate of ARPE-19 cells, with significant differences observed at 200 mW/cm2 (P<0.001) and extremely significant differences at 300 mW/cm2 (P<0.0001). Additionally, compared to commercially available IOLs, LRM had a higher number of cells adhering to their surface (P<0.05), as well as a significantly greater number of adherent bacterium (P<0.0001). CONCLUSION: LRM, characterized by their excellent non-contact tunable deformability and low cytotoxicity to ocular tissues, show considerable potential for use in the fabrication of AIOLs. These materials demonstrate strong cell adhesion; however, during photothermal conversion processes involving shape deformation under various light intensities, the resultant temperature rise may harm surrounding cells. These factors suggest that while the material plays a positive role in reducing the incidence of posterior capsule opacification (PCO), it also poses potential risks for retinal damage. Additionally, the strong bacterial adhesion of these materials indicates an increased risk of endophthalmitis.